Diagnostic value of interferon-γ release assay in HIV-infected individuals complicated with active tuberculosis: a systematic review and meta-analysis. (23rd August 2021) - Ma, Yiyun; Xu, Yuni; Cao, Xiaoqiang; Chen, Xiaojuan; Zhong, Yeteng
Abstract: Objective: Although the interferon- γ release assay (IGRA) has become a common diagnostic method for tuberculosis, its value in the diagnosis of tuberculosis in human immunodeficiency virus (HIV) seropositive patients remains controversial. Therefore, this systematically reviews the data for exploring the diagnostic value of IGRA in HIV-infected individuals complicated with active tuberculosis, aiming to provide a clinical basis for future clinical diagnosis of the disease. Methods: Relevant studies on IGRA for diagnosing tuberculosis in HIV-infected patients were comprehensively collected from Excerpta Medica Database (EMBASE), Medline, Cochrane Library, Chinese Sci-tech Periodical Full-text Database, Chinese Periodical Full-text Database, China National Knowledge Infrastructure (CNKI) and China Wanfang Data up to July 2020. Subsequently, Stata 15.0, an integrated statistical software, was used to analyse the sensitivity, specificity, diagnostic odds ratio (DOR), positive likelihood ratio (PLR) and negative likelihood ratio (NLR) to create receiver operator characteristic (ROC) curves. Results: A total of 18 high-quality articles were selected, including 20 studies, 11 of which were related to QuantiFERON-TB Gold In-Tube (QFT-GIT) and nine to T-SPOT.TB. The meta-analysis indicated that the pooled sensitivity = 0.75 (95% CI 0.63–0.85), the pooled specificity = 0.82 (95% CI 0.66–0.92), PLR = 4.25 (95% CI 1.97–9.18), NLR = 0.30 (95% CI 0.18–0.50), DOR = 14.21 (95% CI 4.38–46.09) and the area under summary ROC curve was 0.85 (95% CI 0.81–0.88). Conclusion: IGRA has a good diagnostic value and therefore can aid in the preliminary screening of active tuberculosis in HIV-infected individuals. Its diagnostic effectiveness can be improved by modifying and optimizing the assay design.